2018
DOI: 10.15171/jrip.2018.45
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of acute antibody mediated rejection in renal allograft biopsies as detected by morphological findings and C4d immunostaining

Abstract: Acute antibody-mediated rejection (AMR) has emerged as an important reason of allograft dysfunction. Histopathologic assessment of post-transplant renal biopsies was routinely performed in many canters for AMR. C4d has emerged as an easy and inexpensive means of detection of AMR. With its help in combination with histopathological findings, AMR can be timely diagnosed. These patients could be benefited from anti-humoral therapy and prevented from more intense rejection in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
0
1
Order By: Relevance
“…On the contrary, C4d positivity in the study conducted by Tariq and Nasir, 2018, was encountered in (16/60, 26.7%) with score 2 in 20% and score 3 in 80%. The reasons for this discrepancy include techniques applied for immunostaining (IF was used in their study) and sample size [35]. In the current study, all cases of ABMR showed evidence of MVI; however, Tariq and Nasir, 2018, found that 6.25% of ABMR cases showed only ATI without evidence of MVI [35].…”
Section: Figure 2: Cases Of Acute T Cell-mediated Rejection Showing: (A) Moderate Interstitial Lymphocytic Infiltrate With Tubular Epithecontrasting
confidence: 52%
“…On the contrary, C4d positivity in the study conducted by Tariq and Nasir, 2018, was encountered in (16/60, 26.7%) with score 2 in 20% and score 3 in 80%. The reasons for this discrepancy include techniques applied for immunostaining (IF was used in their study) and sample size [35]. In the current study, all cases of ABMR showed evidence of MVI; however, Tariq and Nasir, 2018, found that 6.25% of ABMR cases showed only ATI without evidence of MVI [35].…”
Section: Figure 2: Cases Of Acute T Cell-mediated Rejection Showing: (A) Moderate Interstitial Lymphocytic Infiltrate With Tubular Epithecontrasting
confidence: 52%